PEER GROUP SUPPORT DALAM MENINGKATKAN PERILAKU PENCEGAHAN ANEMIA IBU HAMIL - Ria Ines N; Kusnanto Kusnanto; Ni Ketut Alit (Universitas Airlangga, 2014)
Pregnancy is a new period of life, where the baby growth before they were ready to born. Pregnancy closelyassociated with anemia, which Hb amount of mother under 11gr% on first and third trimester, and under10.5gr% on second trimester. Lack of knowledge can lead to inappropriate attitudes and actions in reduce theincidence of anemia. Peer group support which is discuss about the same health problem was untried before. Thepurpose of this study was to analyze the influence of peer group support to knowledge, attitudes, and actions ofpregnant women on anemia prevention during pregnancy. This is a pre-experiments study with one grouppretest-posttest design. Population of this study consist of 156 pregnant women. This research using purposivesampling method. The number of samples is 16 respondents. Independent variable of this study is peer group support,while the dependent variables are knowledge, attitudes and actions. Data collected by observation and questionnaires.The data analyzed with Wilcoxon Signed Rank Test with significance level p < 0.05. Peer group support has asignificant influences in increasing knowledge level, attitudes and actions of pregnant woman. Knowledge analysis testresults: 0.001, attitudes: 0.001 and actions: 0.001. It shows there are significant differences of knowledge, attitudesand actions between before and after peer group support. Peer group support can improve knowledge, attitudesand actions of pregnant woman on anemia prevention. Peer group support helps pregnant woman to get manyinformations from the other members and also help them to find a way out of her problems about anemia prevention. Thismay be a suggestion for the health provider to organize peer group support regularly to increase the knowledge, attitudesand actions of pregnant woman in effort to decrease the incidence of anemia in pregnant woman.